2016
DOI: 10.14309/crj.2015.95
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Panniculitis Associated With Vibrio cholerae Infection

Abstract: We report the first case of acute Vibrio cholerae infection with computed tomography (CT) changes consistent with mesenteric panniculitis (MP). A 78-year-old Indian man returned from overseas travel with progressively severe nausea, vomiting, abdominal pain, and watery diarrhea. His stool tested positive twice for Vibrio cholerae. CT revealed prominent lymph nodes and a hazy mesentery consistent with MP. Antibiotic treatment resulted in complete resolution of MP on follow-up CT 8 months later. In the setting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Several atypical microorganisms such as Cryptococcus neoformans and Mycobacterium genavense have been reported in HIV patients in relation to MP [14,15]. On the other hand, M. tuberculosis and Vibrio cholera are suspected to be the infectious agents that cause MP in immunocompetent patients [16,17]. In addition, various acute abdominal inflammatory disorders in which enteric bacteria was involved in the etiopathogenesis, such as diverticulitis and acute appendicitis, have been reported in relation to MP [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several atypical microorganisms such as Cryptococcus neoformans and Mycobacterium genavense have been reported in HIV patients in relation to MP [14,15]. On the other hand, M. tuberculosis and Vibrio cholera are suspected to be the infectious agents that cause MP in immunocompetent patients [16,17]. In addition, various acute abdominal inflammatory disorders in which enteric bacteria was involved in the etiopathogenesis, such as diverticulitis and acute appendicitis, have been reported in relation to MP [18].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of conditions are associated with MP including abdominal trauma[4], lymphoma and other neoplasms[5,6] and autoimmune diseases[7-9]. Infectious associations with MP include mycobacterial[10] and cryptococcal[11] infections and cholera[12]. In some patients, especially those having an acute presentation of the disease, a viral mesenteritis is likely.…”
Section: Introductionmentioning
confidence: 99%
“…The misty mesentery sign can occur in various conditions, like trauma, abdominal cancer, and infections (3). Regarding the latter, Roginsky et al described it in one patient with Vibrio Cholerae but it was not previously reported in COVID-19 patients (4). The fact that in our cohort the misty mesentery sign was associated with higher levels of CRP lets us assume that the hyperinflammation due to COVID-19 may be the cause (5).…”
mentioning
confidence: 49%